The calculation of the optical gap energy of ZnXO (X = Bi, Sn and Fe) - Benramache Said; Benhaoua Boubaker (Open Physics, 2016)
In this paper, a new mathematical model has been developed to calculate the optical properties of nano materials a function of their size and structure. ZnO has good characterizatics in optical, electrical, and structural crystallisation; We will demonstrate that the direct optical gap energy of ZnO films grown by US and SP spray deposition can be calculated by investigating the correlation between solution molarity, doping levels of doped films and their Urbache energy. A simulation model has been developed to calculate the optical band gap energy of undoped and Bi, Sn and Fe doped ZnO thin films. The measurements by thus proposed models are in agreement with experimental data, with high correlation coefficients in the range 0.94-0.99. The maximum calculated enhancement of the optical gap energy of Sn doped ZnO thin films is always higher than the enhancement attainable with an Fe doped film, where the minimum error was found for Bi and Sn doped ZnO thin films to be 2,345 and 3,072%, respectively. The decrease in the relative errors from undoped to doped films can be explained by the good optical properties which can be observed in the fewer number of defects as well as less disorder.